Association of sleep duration and sleep quality with cognitive frailty in Chinese older adults - Jinqiang Qian; Xin Yu; Qiang Zhang (Frontiers in Public Health)
ObjectiveTo explore the relationship between sleep duration, sleep quality and the occurrence of cognitive frailty in the older adults.MethodsA total of 9,970 participates were screened in China over the past 9 years. They were divided into cognitive frailty group and non-cognitive frailty groups, and they were evaluated for sleep duration and sleep quality and their relationship with cognitive frailty was analyzed. If interactions are found, further hierarchical analysis is conducted.ResultsOne thousand six hundred eighty-four participants (16.89%) were diagnosed with cognitive frailty. Participants with cognitive frailty were more likely to be “unmarried,” live in rural areas, and were female, with no social activity in the last month. Poor sleep quality, short sleep duration, no napping, and excessive napping are at high risk of cognitive frailty. There was a significant interaction between daytime napping and sleep duration and sleep quality. Among participants with good sleep quality, those who took excessive naps had a 123% increased risk of developing cognitive frailty, with an OR of 2.23 (95% CI: 1.72, 2.86). In the subgroup with sleep duration > 9 h, participants who napped excessively had a significantly increased risk of cognitive frailty (OR = 1.62, 95% CI 1.14–2.30, p < 0.001).ConclusionChinese older adults with poor sleep quality are at a 67% higher risk of cognitive weakness, and individuals with less than 6 h of sleep are at a 48% higher risk of cognitive weakness; No napping and excessive napping, the risk of cognitive debilitation increased by 23 and 69%, respectively. There is an additive interaction between sleep duration and quality and daytime napping on cognitive frailty in the older adults.